Thermoplastic Dielectric Elastomer of Triblock Copolymer with High Electromechanical Performance. Issue 16 (3rd July 2017) - Ma, Zipeng; Xie, Yuhan; Mao, Jie; Yang, Xuxu; Li, Tiefeng; Luo, Yingwu
Abstract : Well‐designed polystyrene‐poly(n‐butyl acrylate)‐polystyrene triblock copolymer (SBAS) shows attractive electromechanical performance. Driven by an external electric field, the SBAS actuator shows about 100% static actuation area strain and excellent dynamic performance with a wide half bandwidth of 300 Hz and very high specific power of 1.2 W g –1 within the excitation frequency range 300–800 Hz. Abstract : Dielectric elastomer (DE) actuators have been shown to have promising applications as soft electromechanical transducers in many emerging technologies. The DE actuators, which are capable of large actuation strain over a wide range of excitation frequencies, are highly desirable. Here, the first single‐component DE of a triblock copolymer with attractive electromechanical performance is reported. Symmetric poly(styrene‐ b ‐butyl acrylate‐ b ‐styrene) (SBAS) is designed and synthesized. The SBAS actuator exhibits about 100% static actuation area strain and excellent dynamic performance, as evidenced by a wide half bandwidth of 300 Hz and a very high specific power of 1.2 W g –1 within the excitation frequency range of 300–800 Hz.